1974
DOI: 10.1071/ph740549
|View full text |Cite
|
Sign up to set email alerts
|

2700 MHz Polarization Observations of 17 Supernova Remnants

Abstract: Maps are presented of the polarization and total-power emission at 2700 MHz from 17 supernova remnants, including the Monoceros nebula, the Lupus loop and W44. Directions of the magnetic field and values of the rotation measure are deduced for W44 by combining 2700 and 5000 MHz observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 3 publications
4
21
0
Order By: Relevance
“…G192.8−1.1 is not a SNR G192.8−1.1 (PKS 0607+17) has been proposed as a SNR with an angular extent of about 80 (Milne & Hill 1969;Caswell 1970). The non-thermal spectral index derived was α ∼ −0.5 (Milne & Dickel 1974;Dickel & Denoyer 1975). Berkhuijsen (1974) suggested that G192.8−1.1 is a small part of an even larger SNR, which she called the "Origem Loop" with a diameter of about 5 • , but later Caswell (1985) performed high angular resolution (∼1 ) observations at λ21 cm using the DRAO synthesis telescopes and argued again that G192.8−1.1 is a discrete SNR with a radio spectral index of α ∼ −0.55.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G192.8−1.1 is not a SNR G192.8−1.1 (PKS 0607+17) has been proposed as a SNR with an angular extent of about 80 (Milne & Hill 1969;Caswell 1970). The non-thermal spectral index derived was α ∼ −0.5 (Milne & Dickel 1974;Dickel & Denoyer 1975). Berkhuijsen (1974) suggested that G192.8−1.1 is a small part of an even larger SNR, which she called the "Origem Loop" with a diameter of about 5 • , but later Caswell (1985) performed high angular resolution (∼1 ) observations at λ21 cm using the DRAO synthesis telescopes and argued again that G192.8−1.1 is a discrete SNR with a radio spectral index of α ∼ −0.55.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was difficult to determine the boundary of the SNR, and reliable integrated flux densities could not be obtained. Early λ11 cm polarization observations were made by Milne & Dickel (1974), but no significant polarized emission was detected.…”
Section: G2055+05 (Monoceros Nebula)mentioning
confidence: 99%
“…Observations at frequencies near 2700 MHz were made by Day et al (1972); Milne & Dickel (1974); Velusamy & Kundu (1974); Graham et al (1982). Graham et al (1982) found an average spectral index α = −0.47 ± 0.06 from 111−2700 MHz radio data.…”
Section: Introductionmentioning
confidence: 99%
“…Combining this observation with Effelsberg 21 cm and 11 cm data, they obtained a spectral index of α = −0.43 ± 0.12 for the western shell. Early 11 cm polarization observations were made by Milne & Dickel (1974), but no significant polarized emission was detected. The 6 cm polarization map showed that the magnetic field is closely aligned with the filamentary shell.…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered to be a supernova remnant (SNR) by several researchers (e.g., Caswell 1970;Day et al 1972;Milne & Dickel 1974;Dickel & Denoyer 1975) due to its non-thermal radio spectral index. Berkhuijsen (1974) has also proposed that it is a part of the Origem Loop, a large, 5 ¥ -sized continuum shell, rather than an individual SNR.…”
Section: Introductionmentioning
confidence: 99%